Colour moves : art and fashion by Sonia Delaunay - McQuaid, Matilda; Baumann, Caroline; de Leeuw-de Monti, Matteo; Moggridge, Bill; Timmer, Petra (London : Thames & Hudson, 2011)
Published to accompany a major exhibition at the Smithsonian Institution in New York City, this title focuses not only on abstract painter and colourist Sonia Delaunays art but also her avant-garde fashion designs from her own Atelier Simultane in Paris during the 1920s.
boek